KAJIAN BELANJA WISATAWAN DAN PENYERAPAN TENAGA KERJA BAGI MASYARAKAT SEKITAR TAMAN WISATA ALAM GROJOGAN SEWU TAWANGMANGU - , Dwi Handayani, Prof. Dr. Ir. Chafid Fandeli, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research aim to find out the tourist characteristic at Grojogan Sewu Tawangmangu nature tourism park, type and amount of tourist expenditure at Grojogan Sewu Tawangmangu nature tourism park, factors which influence tourist expenditure amount at Grojogan Sewu Tawangmangu nature tourism park, and employment number in tourism sector employed from local people of Grojogan Sewu Tawangmangu nature tourism park. The research held at Grojogan Sewu Tawangmangu nature tourism park, Karanganyar regency, Central Java province and tourism industry around Grojogan Sewu is analyzed by double linier analysis. Entrepreneurs sample is taken with sampling intensity 10-15% of the population thus the data is analyzed with employment percentage in tourism sector and work force number in tourism sector. The research results are as follows : (1) Grojogan Sewu Tawangmangu nature tourism park tourists are dominated by male tourist, age between 15-30 years old, originated from Central Java province and DIY (except Karanganyar regency), educated, occupation type is student, income less than Rp. 500.000, travel to the location by motor cycle, accompanied by friend and family, visit duration is 1-3 hours and has been visiting Grojogan Sewu Tawangmangu nature tourism park for more than three times (2) The biggest portion of tourist expenditure is for lodging Rp. 141.389/person (46,77%), transportation Rp. 41.430/person (13,71 %), souvenirs Rp. 24.550/orang (8,121%), food and beverage Rp. 22.082/person (7,305%), photography and horse rent Rp. 15.000/person (5%), swimming pool and flying fox Rp. 10.000/person (3%), entry ticket, parking, helmet keeping service, toilet rent, mat and umbrella rent Rp.1.000-Rp.3.000/person (1%). (3) Double linier analysis result shows R2 = 0,474. It means 47,40% tourist expenditure is influenced by income and visiting duration. The remain 52,60 % is influenced by other variables which are not included in the model (4) Local employment around Grojogan Sewu Tawangmangu nature tourism park in tourism sector is estimated around 18,60 %. Employment in the business sector shows that for average, every two tourists can give work opportunity for one person of tourism service playmaker at Grojogan Sewu Tawangmangu nature tourism park.